MAL, Menyusui, Kontrasepsi FREKUENSI MENYUSUI DENGAN KEBERHASILAN KONTRASEPSI METODE AMENORHEA LAKTASI (MAL) DI KECAMATAN KRANGGAN KOTA MOJOKERTO - Dhonna Anggraeni (Jurnal Keperawatan Malang, 2017)
Abstract The fact is they are a lot of nursing mother haven’t been aware of the importance of breastfeeding, especially as a natural contraseptive. The purpose of the study was to determine the relationship of the frequency of breasfeeding success MAL contraception in the subdistrict Kranggan City of Mojokerto. The type of this study is observational analytic with the cross sectional design. The population was all mothers breastfeed exclusively for 0-6 months and not using contraception at after giving birth as many as 42 mothers and get sample of 38 respondents and taken by simple random sampling method. Analyzed usid Chi – square test. Results of the Chi Square obtained X2 count = 4.32> = X2 table 3,84 then H1 is accepted, it means there was correlation between breastfeeding frequency relationship to the success of lactation amenorrhea method of contraception. The more frequently a mother breastfeeding her baby in a day then the longer the delay in womenovulation. This study is expeccted to be new information source for health workers in determining health care policy. Keywords: Breastfeeding Frequency, Contraception, MAL